Warfarin: Pharmacology and Factors Affecting its Response - Wattanachai, Nitsupa; Kaewmoongkun, Sutthida (Srinagarind Medical Journal, 2017)
Abstract Warfarin is the most widely used oral anticoagulant. Its indication is the prevention or treatment of thromboembolism. Although warfarin is highly effective, it has several limitations because of its narrow therapeutic index and the large inter-individual variability in dosing requirement making it a very problematic drug to prescribe. Several factors can affect the patients’ response to warfarin. Genetic polymorphisms in cytochrome P450 2C9 (CYP2C9) encoding CYP2C9 enzyme, the major drug metabolizing enzyme of S-warfarin, and vitamin K 2, 3-epoxide reductase complex subunit 1 (VKORC1), the target enzyme of warfarin, taken together with age, body mass index, and drug interactions explained 59% of warfarin dose-response variability. In addition, environmental factors (such as alcohol drinking and smoking) can also affect the variability in warfarin response. The purpose of this review is to gather the knowledge about the pharmacology of warfarin and the factors affecting warfarin response. This useful information will improve the efficacy and safety of warfarin therapy. เภสัชวิทยาและปัจจัยที่มีผลต่อการตอบสนองของยาวาร์ฟาริน นิตย์สุภา วัฒนชัย, สุทธิดา แก้วมุงคุณ ภาควิชาเภสัชวิทยา คณะแพทยศาสตร์ มหาวิทยาลัยขอนแก่น ขอนแก่น ยาวาร์ฟารินเป็นยาต้านการแข็งตัวของเลือดชนิดรับประทานซึ่งใช้รักษาอย่างแพร่หลาย มีข้อบ่งใช้คือเพื่อป้องกันภาวะเสี่ยงหรือรักษาโรคลิ่มเลือดอุดตัน แม้ว่ายาวาร์ฟารินมีประสิทธิภาพในการรักษาดี แต่เนื่องจากยาวาร์ฟารินมีช่วงการรักษาแคบ อีกทั้งมีความแปรปรวนระหว่างบุคคลในการรักษาสูง จึงทำให้การปรับขนาดยาวาร์ฟารินให้อยู่ในช่วงการรักษายังคงมีปัญหา มีหลายปัจจัยที่ส่งผลต่อการตอบสนองต่อยาวาร์ฟาริน ได้แก่ ภาวะพหุสัณฐานทางพันธุกรรมของยีน cytochrome P450 2C9 (CYP2C9) ที่ควบคุมการสร้างเอนไซม์ CYP2C9 ซึ่งทำหน้าที่เปลี่ยนสภาพยาวาร์ฟาริน และยีน vitamin K epoxide reductase complex subunit 1 (VKORC1) ซึ่งเป็นตำแหน่งออกฤทธิ์ของยาวาร์ฟารินร่วมกับอายุ ดัชนีมวลกาย และการเกิดอันตรกิริยากับยาอื่นที่ใช้ร่วม คิดเป็นร้อยละ 59 ที่ส่งผลต่อความแปรปรวนในการตอบสนองต่อยาวาร์ฟาริน นอกจากนั้นพบว่าปัจจัยทางสิ่งแวดล้อม (เช่น การดื่มแอลกอฮอล์ การสูบบุหรี่) ส่งผลต่อความแปรปรวนในการตอบสนองต่อยาวาร์ฟารินอีกด้วย การทบทวนวรรณกรรมนี้มุ่งประมวลองค์ความรู้ที่เกี่ยวข้องกับเภสัชวิทยาของยาวาร์ฟารินและปัจจัยต่าง ๆ ที่มีผลต่อการตอบสนองต่อยาวาร์ฟาริน ซึ่งจะเป็นข้อมูลที่เป็นประโยชน์สำหรับการรักษาด้วยยาวาร์ฟารินให้เป็นไปอย่างมีประสิทธิภาพและมีความปลอดภัยยิ่งขึ้น